TELEMETRY SYSTEM OF UNMANNED AERIAL VEHICLES - Vasylenko, M. P.; Karpyuk, I. S. (Electronics and Control Systems, 2018)
The article is devoted to the design of unmanned aerial vehicles telemetry system software based on MAVLink protocol. Telemetry systems are necessary for most of the unmanned aerial vehicle types even with small operating range to inform operator about restricted areas and battery charge. More advanced unmanned aerial vehicles must also report piloting and navigation parameters, route details and current task progress parameters. It requires unmanned aerial vehicle to use special hardware and software equipment so it is necessary to make it energy effective. This problem can be solved using package data transmission protocols.